Comparison of feature selection and classification combinations for cancer classification using microarray data - Vijayan, V.; Bulsara, B.; Gadgil, Chetan J.; Gadgil, Mugdha (International Journal of Bioinformatics Research and Applications, 2009)

Controlled release of nutrients to mammalian cells cultured in shake flasks - Hegde, Swati; Pant, Tejal; Pradhan, Ketaki; Badiger, Manohar V.; Gadgil, Mugdha (Biotechnology Progress, 2012)
Though cell culture-based protein production processes are rarely carried out under batch mode of operation, cell line and initial process development operations are usually carried out in batch mode due to simplicity of operation in widely used scale down platforms like shake flasks. Nutrient feeding, if performed, is achieved by bolus addition of concentrated feed solution at different intervals, which leads to large transient increases in nutrient concentrations. One negative consequence is increased waste metabolite production. We have developed a hydrogel-based nutrient delivery system for continuous feeding of nutrients in scale down models like shake flasks without the need for manual feed additions or any additional infrastructure. Continuous delivery also enables maintaining nutrient concentrations at low levels, if desired. The authors demonstrate the use of these systems for continuous feeding of glucose and protein hydrolysate to a suspension Chinese Hamster Ovary (CHO) culture in a shake flask. Glucose feeding achieved using the glucose-loaded hydrogel resulted in a 23% higher integral viable cell density and an 89% lower lactate concentration at the end of the culture when compared with a bolus-feed of glucose. (c) 2011 American Institute of Chemical Engineers Biotechnol. Prog., 2012

Comparison of methods for identifying periodically varying genes - Vijayan, V.; Deshpande, P.; Gadgil, Chetan J.; Gadgil, Mugdha (International Journal of Bioinformatics Research and Applications, 2013)

Cell line development for biomanufacturing processes: recent advances and an outlook - Le, Huong; Vishwanathan, Nandita; Jacob, Nitya M.; Gadgil, Mugdha; Hu, Wei-Shou (Biotechnology Letters, 2015)
At the core of a biomanufacturing process for recombinant proteins is the production cell line. It influences the productivity and product quality. Its characteristics also dictate process development, as the process is optimized to complement the producing cell to achieve the target productivity and quality. Advances in the past decade, from vector design to cell line screening, have greatly expanded our capability to attain producing cell lines with certain desired traits. Increasing availability of genomic and transcriptomic resources for industrially important cell lines coupled with advances in genome editing technology have opened new avenues for cell line development. These developments are poised to help biosimilar manufacturing, which requires targeting pre-defined product quality attributes, e.g., glycoform, to match the innovator's range. This review summarizes recent advances and discusses future possibilities in this area.
Keywords: Biomanufacturing; Biosimilars; Cell line development; CHO cells genomics; Genome editing; Transcriptomics

Cell culture processes for biopharmaceutical manufacturing - Gadgil, Mugdha (Current Science, 2017)
Recombinant proteins manufactured using animal cell culture processes comprise a significant fraction of biopharmaceuticals. With the expiry of patents on this class of therapeutics, there is also a significant interest in manufacture of biosimilar versions of such therapeutics. This article provides a birds-eye view of upstream process development for animal cell culture processes, with a focus on advances pertinent to the development of processes for biosimilars.
Keywords: Biopharmaceutical; Cell line development; CHO; glycosylation; monoclonal antibody

CHO Cells Adapted to Inorganic Phosphate Limitation Show Higher Growth and Higher Pyruvate Carboxylase Flux in Phosphate Replete Conditions - Maralingannavar, Vishwanathgouda; Parmar, Dharmeshkumar; Pant, Tejal; Gadgil, Chetan; Panchagnula, Venkateswarlu; Gadgil, Mugdha (Biotechnology progress, 2017)
Inorganic phosphate (P-i) is an essential ion involved in diverse cellular processes including metabolism. Changes in cellular metabolism upon long term adaptation to P-i limitation have been reported in E. coli. Given the essential role of P-i, adaptation to P-i limitation may also result in metabolic changes in animal cells. In this study, we have adapted CHO cells producing recombinant IgG to limiting P-i conditions for 75 days. Not surprisingly, adapted cells showed better survival under P-i limitation. Here, we report the finding that such cells also showed better growth characteristics compared to control in batch culture replete with P-i ( higher peak density and integral viable cell density), accompanied by a lower specific oxygen uptake rate and cytochrome oxidase activity towards the end of exponential phase. Surprisingly, the adapted cells grew to a lower peak density under glucose limitation. This suggests long term P-i limitation may lead to selection for an altered metabolism with higher dependence on glucose availability for biomass assimilation compared to control. Steady state U-C-13 glucose labeling experiments suggest that adapted cells have a higher pyruvate carboxylase flux. Consistent with this observation, supplementation with aspartate abolished the peak density difference whereas supplementation with serine did not abolish the difference. This supports the hypothesis that cell growth in the adapted culture might be higher due to a higher pyruvate carboxylase flux. Decreased fitness under carbon limitation and mutations in the sucABCD operon has been previously reported in E. coli upon long term adaptation to P-i limitation, suggestive of a similarity in cellular response among such diverse species. (C) 2017 American Institute of Chemical Engineers